# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = 2 x y^{2}+3 x^{2} y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 6 \,{\mathrm e}^{2 x -y}
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime } \sqrt {x} = \cos \left (y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 2
\] |
✓ |
✓ |
|
\[
{}-2 y+y^{\prime } = 3 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}3 y+y^{\prime } = 2 x \,{\mathrm e}^{-3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 x y = {\mathrm e}^{x^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+2 y = 3 x
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }+y = 10 \sqrt {x}
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }+y = 10 \sqrt {x}
\] |
✓ |
✓ |
|
\[
{}y+3 x y^{\prime } = 12 x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }-3 y = 9 x^{3}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = 3 x y
\] |
✓ |
✓ |
|
\[
{}3 y+x y^{\prime } = 2 x^{5}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}-3 y+x y^{\prime } = x^{3}
\] |
✓ |
✓ |
|
\[
{}2 x y+y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (1-y\right ) \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y+\left (1+x \right ) y^{\prime } = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x^{3} \cos \left (x \right )+2 y
\] |
✓ |
✓ |
|
\[
{}y \cot \left (x \right )+y^{\prime } = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+x +y+x y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 3 y+x^{4} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x^{2} {\mathrm e}^{x^{2}}+2 x y
\] |
✓ |
✓ |
|
\[
{}\left (2 x -3\right ) y+x y^{\prime } = 4 x^{4}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+4\right ) y^{\prime }+3 x y = x
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+3 x^{3} y = 6 x \,{\mathrm e}^{-\frac {3 x^{2}}{2}}
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right ) y^{\prime } = x -y
\] |
✓ |
✓ |
|
\[
{}2 x y y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+2 \sqrt {x y}
\] |
✓ |
✓ |
|
\[
{}\left (x -y\right ) y^{\prime } = x +y
\] |
✓ |
✓ |
|
\[
{}x \left (x +y\right ) y^{\prime } = y \left (x -y\right )
\] |
✓ |
✓ |
|
\[
{}\left (x +2 y\right ) y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{2} y^{\prime } x = y^{3}+x^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = x^{2} {\mathrm e}^{\frac {y}{x}}+x y
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = x y+y^{2}
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = x^{2}+3 y^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-y^{2}\right ) y^{\prime } = 2 x y
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = y^{2}+x \sqrt {4 x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+\sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x +y y^{\prime } = \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}y \left (3 x +y\right )+x \left (x +y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {x +y+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (y+4 x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y+x^{2} y^{\prime } = 5 y^{3}
\] |
✓ |
✓ |
|
\[
{}2 x y^{3}+y^{\prime } y^{2} = 6 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y+y^{3}
\] |
✓ |
✓ |
|
\[
{}2 x y+x^{2} y^{\prime } = 5 y^{4}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+6 y = 3 x y^{{4}/{3}}
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }+y^{3} {\mathrm e}^{-2 x} = 2 x y
\] |
✓ |
✓ |
|
\[
{}\sqrt {x^{4}+1}\, y^{2} \left (x y^{\prime }+y\right ) = x
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime } y^{2}+y^{3} = {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}3 y^{2} y^{\prime } x = 3 x^{4}+y^{3}
\] |
✓ |
✓ |
|
\[
{}x \,{\mathrm e}^{y} y^{\prime } = 2 \,{\mathrm e}^{y}+2 x^{3} {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}2 x \sin \left (y\right ) \cos \left (y\right ) y^{\prime } = 4 x^{2}+\sin \left (y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}\left ({\mathrm e}^{y}+x \right ) y^{\prime } = x \,{\mathrm e}^{-y}-1
\] |
✓ |
✓ |
|
\[
{}2 x +3 y+\left (2 y+3 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 x -y+\left (6 y-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2}+2 y^{2}+\left (4 x y+6 y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2}+2 x y^{2}+\left (2 x^{2} y+4 y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{3}+\frac {y}{x}+\left (y^{2}+\ln \left (x \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+{\mathrm e}^{x y} y+\left (2 y+x \,{\mathrm e}^{x y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right )+\ln \left (y\right )+\left ({\mathrm e}^{y}+\frac {x}{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +\arctan \left (y\right )+\frac {\left (x +y\right ) y^{\prime }}{1+y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y^{3}+y^{4}+\left (3 y^{2} x^{3}+4 x y^{3}+y^{4}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x} \sin \left (y\right )+\tan \left (y\right )+\left ({\mathrm e}^{x} \cos \left (y\right )+x \sec \left (y\right )^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {2 x}{y}-\frac {3 y^{2}}{x^{4}}+\left (\frac {2 y}{x^{3}}-\frac {x^{2}}{y^{2}}+\frac {1}{\sqrt {y}}\right ) y^{\prime } = 0
\] |
✗ |
✓ |
|
\[
{}\frac {2 x^{{5}/{2}}-3 y^{{5}/{3}}}{2 x^{{5}/{2}} y^{{2}/{3}}}+\frac {\left (-2 x^{{5}/{2}}+3 y^{{5}/{3}}\right ) y^{\prime }}{3 x^{{3}/{2}} y^{{5}/{3}}} = 0
\] |
✓ |
✓ |
|
\[
{}x^{3}+3 y-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{2}+x y^{2}-x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y+y^{2}-x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x}+2 x y^{3}+\left (3 x^{2} y^{2}+\sin \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 y+x^{4} y^{\prime } = 2 x y
\] |
✓ |
✓ |
|
\[
{}2 x y^{2}+x^{2} y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y+x^{3} y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}2 x y+x^{2} y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+2 y = 6 x^{2} \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+x^{2}+y^{2}+x^{2} y^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = x y+3 y^{2}
\] |
✓ |
✓ |
|
\[
{}6 x y^{3}+2 y^{4}+\left (9 x^{2} y^{2}+8 x y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+x^{2}+y^{2}+x^{2} y^{4}
\] |
✗ |
✗ |
|
\[
{}x^{3} y^{\prime } = x^{2} y-y^{3}
\] |
✓ |
✓ |
|
\[
{}3 y+y^{\prime } = 3 x^{2} {\mathrm e}^{-3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-2 x y+x^{2}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x}+{\mathrm e}^{x y} y+\left ({\mathrm e}^{y}+x \,{\mathrm e}^{x y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y-x^{3} y^{\prime } = y^{3}
\] |
✓ |
✓ |
|
\[
{}3 x^{5} y^{2}+x^{3} y^{\prime } = 2 y^{2}
\] |
✓ |
✓ |
|
\[
{}3 y+x y^{\prime } = \frac {3}{x^{{3}/{2}}}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime }+\left (x -1\right ) y = 1
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 12 x^{4} y^{{2}/{3}}+6 y
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{y}+y \cos \left (x \right )+\left (x \,{\mathrm e}^{y}+\sin \left (x \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}9 x^{2} y^{2}+x^{{3}/{2}} y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}2 y+\left (1+x \right ) y^{\prime } = 3 x +3
\] |
✓ |
✓ |
|
\[
{}9 \sqrt {x}\, y^{{4}/{3}}-12 x^{{1}/{5}} y^{{3}/{2}}+\left (8 x^{{3}/{2}} y^{{1}/{3}}-15 x^{{6}/{5}} \sqrt {y}\right ) y^{\prime } = 0
\] |
✗ |
✓ |
|
\[
{}3 y+y^{4} x^{3}+3 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = 2 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y+\left (2 x +1\right ) y^{\prime } = \left (2 x +1\right )^{{3}/{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 \left (y+7\right ) x^{2}
\] |
✓ |
✓ |
|